2022
DOI: 10.3390/ijerph191912441
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Distribution and the Driving Factors of Carbon Emissions from Urban Production Energy Consumption

Abstract: Urban production energy consumption produces a large amount of carbon emissions, which is an important source of global warming. This study measures the quantity and intensity of carbon emissions in 30 provinces of China based on urban production energy consumption from 2005–2019, and uses the Dagum Gini coefficient, kernel density estimation, carbon emission classification and spatial econometric model to analyze the spatial and temporal distribution and driving factors of quantity and intensity of carbon emi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 76 publications
(77 reference statements)
0
3
0
Order By: Relevance
“…Because changes in land use structure and carbon emission intensity are influenced by numerous factors, we cannot rule out the possibility that there are other more relevant reasons in these places causing them to have a negative association, or is it simply a statistical error caused by data accuracy? According to some studies, China’s industrial carbon emissions have an inverted U-shaped non-linear relationship with the level of economic development [ 48 ], and it is widely assumed that economic development is consistent with the growth of carbon emissions, however, the backward stage of economic development causes more carbon emissions due to resource underutilization. Therefore, we speculate that there may be certain threshold intervals, and when the information entropy of land use structure is within these intervals, the information entropy shows a negative correlation with carbon emission intensity.…”
Section: Discussionmentioning
confidence: 99%
“…Because changes in land use structure and carbon emission intensity are influenced by numerous factors, we cannot rule out the possibility that there are other more relevant reasons in these places causing them to have a negative association, or is it simply a statistical error caused by data accuracy? According to some studies, China’s industrial carbon emissions have an inverted U-shaped non-linear relationship with the level of economic development [ 48 ], and it is widely assumed that economic development is consistent with the growth of carbon emissions, however, the backward stage of economic development causes more carbon emissions due to resource underutilization. Therefore, we speculate that there may be certain threshold intervals, and when the information entropy of land use structure is within these intervals, the information entropy shows a negative correlation with carbon emission intensity.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the spatial difference of CEI, the existing literature mainly uses the coefficient of variation [21,22], the Theil index [23,24], spatial autocorrelation [25,26], and the Gini coefficient [27] to reveal the differences of regional CEI. Yang [28] used the Theil index to study CEI's spatial and temporal distribution and regional differences from 2000 to 2019 in China and found that the decrease in CEI from 2000 to 2019 showed an obvious imbalance in spatial and temporal distribution, in which the gap between the North and the South was larger than that between the East and the West.…”
Section: Introductionmentioning
confidence: 99%
“…Many scholars have calculated the carbon emissions of different industries and sectors, such as industry, agriculture, tourism, and transportation. Studies on carbon emissions from land use [14], carbon emissions from energy consumption [15], and embodied carbon emissions from trade [16] have also gradually increased. Regarding the influencing factors of carbon emissions, related research focuses on urbanization [17], technological innovation [18], energy consumption scale [19], and industrial agglomeration [20], these studies use the LMDI model [21], spatial econometric model [22] and threshold effect to conduct in-depth research.…”
Section: Introductionmentioning
confidence: 99%